Delta-Notch signalling in segmentation. Issue 3 (May 2017) - Liao, Bo-Kai; Oates, Andrew C.
Abstract: Modular body organization is found widely across multicellular organisms, and some of them form repetitive modular structures via the process of segmentation. It's vastly interesting to understand how these regularly repeated structures are robustly generated from the underlying noise in biomolecular interactions. Recent studies from arthropods reveal similarities in segmentation mechanisms with vertebrates, and raise the possibility that the three phylogenetic clades, annelids, arthropods and chordates, might share homology in this process from a bilaterian ancestor. Here, we discuss vertebrate segmentation with particular emphasis on the role of the Notch intercellular signalling pathway. We introduce vertebrate segmentation and Notch signalling, pointing out historical milestones, then describe existing models for the Notch pathway in the synchronization of noisy neighbouring oscillators, and a new role in the modulation of gene expression wave patterns. We ask what functions Notch signalling may have in arthropod segmentation and explore the relationship between Notch-mediated lateral inhibition and synchronization. Finally, we propose open questions and technical challenges to guide future investigations into Notch signalling in segmentation. Highlights: Vertebrate segmentation clocks are different to each other. Notch has a primary role in synchronization in vertebrates. Gene expression waves can influence the timing of segment formation. Synchronization and lateral inhibition circuits are closely related. Dynamic measurement techniques are needed to dissect clocks.